FORMULATION EVALUATION AND OPTIMIZATION OF ORODISPERSIBLE TABLETS OF PANTOPRAZOLE SODIUM BY THE USING OF DIFFERENT SUPERDISINTEGRANTS - Singh Chundawat, Lokendra; Sharma, Vishal (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of this study was to formulate and optimize an orodispersible formulation of pantoprazole sodium using a 32 factorial design for optimized the superdisintegrant concentration. Methods: Various concentrations (2%, 4%, and 6%) of superdisintegrants (sodium starch glycollate [SSG] and crospovidone [CP]) were added in the formulation, all processing steps are carried out at a temperature below 250c and relative humidity <35%. Procedure to manufacture orodispersible tablets by direct compression was established. Results: The results show that the presence of a superdisintegrants is desirable for orodispersion. The best-optimized batch found was the batch having amount of CP 4.37 mg and SSG 10.59 mg. All the formulations satisfied the limits of orodispersion with a dispersion time of <30 s best formulation showed a disintegration time (DT) of 30 s, % friability is 0.82%, drug content of 96– 99.4, and fast drug release rate of 80 % of drug release within 10 min. Conclusion: The optimized batch was evaluated for thickness, weight variation, hardness, friability, DT dissolution, and accelerated stability study for a period of 3 months. The similarity factor was calculated for comparison of dissolution profile before and after stability studies. The f2 value was found more than 50 that indicate a good similarity between both the dissolution profiles. Hence, the results of stability studies reveal that the developed formulation has good stability.